Maternal Satisfaction and Its Associated Factors towards Spinal Anesthesia for Caesarean Section: A Cross-Sectional Study in Two Eritrean Hospitals - Idris Mohammed Idris; Ghidey Gebreyohanns Weldegiorgis; Eyasu Habte Tesfamariam (Anesthesiology Research and Practice)
Objective. Satisfaction of mothers during caesarean section is an important indicator for measuring quality of obstetric anesthesia. This study aimed to determine mothers’ level of satisfaction and the predicting factors of dissatisfaction towards spinal anesthesia during caesarean section. Methods. Cross-sectional study design was utilized in Orotta Maternity Hospital (OMH) and Sembel Hospital from December 2017 to February 2018, in Asmara, Eritrea. Satisfaction of the mothers was measured using a pretested questionnaire. Bivariate and multivariate logistic regression were utilized to identify predictors of dissatisfaction using SPSS (Version 22.0). Results. Involvement of mothers in the choice of anesthesia (3.3%) and explanation about the stay at operating theater (10%) were the two least reported items. As per the subscale analysis, the lowest satisfaction was observed for the preoperative assessment (16.7%). Overall, 87.9% of the mothers were satisfied with the spinal anesthetic service. Hospital at which anesthesia was administered (p<0.001), marital status (p<0.001), and intraoperative pain (p<0.001) were significant predictors of dissatisfaction towards spinal anesthesia. Moreover, the rate of refusal to have spinal anesthesia in the future was 12.5%. Conclusion. Though overall satisfaction can be considered as fair, preoperative assessment is considerably low. Hence, explaining the benefits and risks of the anesthetic techniques as well as considering patient’s opinion is very important while deciding the type of anesthesia.